2015
DOI: 10.1002/adfm.201404510
|View full text |Cite
|
Sign up to set email alerts
|

Lab in a Tube: Purification, Amplification, and Detection of DNA Using Poly(2‐oxazoline) Multilayers

Abstract: Fast and easy purifi cation and amplifi cation of DNA are prerequisites for the development of point-of-care diagnostics. For this reason covalent coatings of amine containing poly(2-oxazoline)s (POx) on glass and poly(propylene) surfaces are prepared, to reversibly bind genetic material directly from biological samples. The polymer is deposited in a layer-by-layer process, whereas initial immobilization of macromolecules on the surface is accomplished by the use of an epoxy functionalized siloxane monolayer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Additionally, the formation of micelles as drug carriers, [51] nanogels [44] and surface coatings for bio-analytics [52] supports the increasing importance of POx.…”
mentioning
confidence: 95%
“…Additionally, the formation of micelles as drug carriers, [51] nanogels [44] and surface coatings for bio-analytics [52] supports the increasing importance of POx.…”
mentioning
confidence: 95%
“…Therefore, the investigated polymers are usable for the purification of genetic material or drug delivery applications, however, not for gene delivery by using the investigated conditions. Future studies might concentrate on alternative copolymers with differences in the hydrophobicity and buffer capacity to identify ideal carriers for genetic material, which can ensure biocompatibility while expressing higher transfection efficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…After the addition of samples to the testing device, the results are displayed within a few minutes. In POC testing, various detection techniques such as nucleic acid testing ( Batule et al, 2020 ; Leiske et al, 2015 ), lateral flow assays (LFA) ( Fang et al, 2014 ; R. H. Tang et al, 2017 ), nanomaterial-based sensors ( Li et al, 2020 ; Liu et al, 2014 ; Ngo et al, 2018 ; Padmavathy et al, 2012 ), colorimetric immunosensors ( Ren et al, 2017 ), volatile organic compound sensors (Z. Li et al, 2019a , Li et al, 2019b ), bio-optical sensors ( Jin et al, 2018 ; Yoo and Lee, 2016 ), and electrochemical sensors ( Dutta et al, 2018 ; W. Liu et al, 2018 ) have been applied for the rapid detection of a broad range of human and plant diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Several on-chip cell lysis techniques such as chemical lysis ( Ma et al, 2019 ; Yoon et al, 2018 ), mechanical lysis (J. Choi et al, 2015 ; Mahalanabis et al, 2009 ), electrical lysis ( Hügle et al, 2018 ; Kim et al, 2009 ; Nan et al, 2014 ), ultrasonic lysis ( Branch et al, 2017 ), thermal lysis ( Leiske et al, 2015 ; Wang et al, 2011 ; Zhang et al, 2016 ), and enzymatic lysis ( Lounsbury et al, 2013 ; Petralia et al, 2013 ) have been demonstrated for rapid lysis of human and pathogen cells.…”
Section: Introductionmentioning
confidence: 99%